Schistosomiasis Mansoni in the Amazon Region: malacological surveys of intermediate hosts for the identification of disease transmission areas in Bel?m, Par?, Brazil - Goveia, Christiane de Oliveira (David Publishing, 2019)
In Brazil, schistosomiasis occurrence is related to the presence of the etiological agent Schistosoma mansoni. The presence of mollusks for Biomphalaria genus is a necessary condition for development of the parasite cycle. In Par? state, the species B. schrammi, B. kuhniana, B. straminea and B. glabrata have already been identified, with reports of the last two occurring in Bel?m. The aim of this study was to determine the spatial distribution of Biomphalaria species in Bel?m, Par?, Brazil, identifying risk areas for schistosomiasis transmission. Biannual malacological surveys were carried out between September 2013 and October 2017 in 35 neighborhoods of Bel?m. The collection points were georeferenced using a Global Positioning System (GPS) receiver and the Kernel Density Estimation (KDE) was used to the spatial analysis. The mollusks, after measurement, were exposed to light to verify the presence of S. mansoni cercariae. Subsequently, mollusks were sacrificed and fixed for dissection and morphological identification of species. The surveys resulted in a total of 10,803 mollusks collected, of which 9,367 (86.70%) specimens were examined. Among the analyzed mollusks, 5,820 (62.14%) were identified as B. glabrata and 3,547 (37.86%) as B. straminea. The presence of the parasite was observed in 208 (2.22%) specimens, all B. glabrata. Positive mollusks were found in six neighborhoods: Guam? (51 mollusks/24.5%), Sacramenta (47 mollusks/22.6%), Tel?grafo (47 mollusks/22.6%), Terra Firme (36 mollusks/17.3%), Condor (20 mollusks/9.6%) and Barreiro (7 mollusks/3.4%). This study confirms that B. glabrata species actively participates as intermediate host in the disease maintenance in Bel?m. The KDE allowed to analyze the spatial distribution of collection sites and consequently to determine possible risk areas of schistosomiasis transmission in Bel?m. The development of maps identifying sites with schistosomiasis positive snails may support efforts of this municipality by directing activities related to endemic disease control.